Jury Trials and Plea Bargaining : a True History. - McConville, Mike (Hart Pub., 2005)
This book is a study of the social transformation of criminal justice, its institutions, its method of case disposition and the source of its legitimacy. Focused upon the apprehension, investigation and adjudication of indicted cases in New York Citys main trial tribunal in the nineteenth century - the Court of General Sessions - it traces the historical underpinnings of a lawyering culture which, in the first half of the nineteenth century, celebrated trial by jury as the fairest and most reliable method of case disposition and then at the middle of the century dramatically gave birth to ple.